Unaccompanied Immigrant Children in ORR Foster Care: Community Level Facilitators of Adjustment Identified by Service Providers. - Evans, Kerri; Hasson III, Robert G.; Teixeira, Samantha; Fitchett, Virginia; Crea, Thomas M. (Child & Adolescent Social Work Journal, 2024)
Purpose: While many studies address immigrant integration, few focus on the adjustment process for unaccompanied immigrant children in foster care in the United States- and even fewer look at community level prevention and intervention strategies for positive youth adjustment. This study uses a human rights framework to examine community level facilitators- both prevention and interventions- that aid the adjustment for unaccompanied immigrant children in foster care as they navigate life in the US. Method: Seventy-nine service providers that work with unaccompanied immigrant children participated in 22 focus groups/interviews. Open coding was used to create a codebook, and then data were qualitatively analyzed using deductive and axial coding. Results: The major prevention strategies for community adjustment include welcoming communities and inter-agency collaborations. The major intervention strategies for systems level adjustment include community relationships, access to healthcare, and the church as an institution. Discussion: Implications include advocating for funding and programming to support mentors for every child, advocating for welcoming policies, and engaging unaccompanied immigrant children in research using participatory approaches.